Pattern of Pap smear cytology: our experience - S., Arul Anne Rose (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To study the pattern of cervical smear abnormalities among patients attending the Gynaecology department in our hospital during the study period, in order to understand the magnitude of the problem in our region and to address the need for effective screening programmes. Methods: It was a hospital based prospective study over a period of six months. According to our study criteria, pap smears were collected and reported. Frequencies of the epithelial abnormalities were calculated. Results: A total of 630 pap smears were collected and reported in our study. Among them 256 were normal smears (40.6%), 362 were abnormal smears (57.5%) and 12 smears were unsatisfactory (1.9%). When we analysed the abnormal smears (362 smears), 338 were negative for intraepithelial lesions or malignancy (93.4% of abnormal smears or 53.7% of total smears), and 24 smears were classified as epithelial lesions (6.6% of abnormal smears or 3.8% of total smears). ASC-US, ASC-H, LSIL, HSIL, AGUS, Atypical endocervical cells and squamous cell carcinoma were found in 0.9%, 0.5%, 0.5%, 0.6%, 0.2%, 0.3% and 0.8% respectively. Conclusions: Our results emphasize that we have to encourage and motivate the women for active screening. It also indicates the need for well-organized screening programmes which already exist in well developed countries in order to reduce the burden of cervical cancer.